2013
DOI: 10.1021/jf403422x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Five Metals on the Evolution of Hydrogen Sulfide, Methanethiol, and Dimethyl Sulfide during Anaerobic Storage of Chardonnay and Shiraz Wines

Abstract: The synergistic effects of Cu, Fe, Mn, Zn, and Al on the evolution of different volatile sulfur compounds (VSCs) in a Chardonnay and a Shiraz wine have been investigated. The evolution of H2S, MeSH, and DMS were influenced by metal addition, and in some instances, a combination of metals was responsible for the largest variation in the concentration of VSCs. The metals and metal combinations associated with significant changes in VSC concentrations in both Chardonnay and Shiraz samples after anaerobic storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 54 publications
2
68
1
Order By: Relevance
“…after bottle ageing) (Ugliano et al 2011b, Viviers et al 2013. after bottle ageing) (Ugliano et al 2011b, Viviers et al 2013.…”
Section: Residual Copper Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…after bottle ageing) (Ugliano et al 2011b, Viviers et al 2013. after bottle ageing) (Ugliano et al 2011b, Viviers et al 2013.…”
Section: Residual Copper Activitymentioning
confidence: 99%
“…In these same wines, however, the hydrogen sulfide concentration often increased during bottle ageing after the wine reached conditions of low dissolved oxygen (Ugliano et al 2011b, 2012, Viviers et al 2013). In a recent industry study on a non-protein stabilised Riesling wine with added copper(II) at a rate of 0.5, 2.5 and 5.0 mg/L, the highest concentration of hydrogen sulfide after 7 months of storage correlated with the highest concentration of residual copper in the wine .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wine with significant concentrations of hydrogen sulfide and methanethiol is sensorially labeled as "reduced", and this is more likely to occur in conditions of low oxygen, as found during bottle aging in screw capped bottles. The role of Cu in this process is complex as it can decrease the volatile component of hydrogen sulfide and thiol compounds when added to wine during wine production but can also lead to an increase in the total concentrations of these thiol compounds when the wine is stored in low oxygen conditions [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It has reported that the functional groups of the carbon surface can be modified either by the chemical and thermal treatments or by the impregnation method (Lee et al, 2010). In addition, alkali metals, alkaline earth metals, transition metal oxides, and rare earth metal oxides are proved to be excellent active component (Fan et al, 2013;Laosiripojana and Assabumrungrat, 2011;Park and Novak, 2013;Viviers et al, 2013;Vega et al, 2013;Laosiripojana et al, 2014).…”
Section: Introductionmentioning
confidence: 99%